A Survey Paper on Smart Health Monitoring of Quarantined People - Lithin Kumble, Ravi Shankar H., Dr. Vishwanath Y., Dasari Bhulakshmi, Laxmi B. Rananavare, Gopinath R., Supreeth S. (International Journal of Advanced Science and Technology, 2020)
Covid-19  has given a new dimension to human lives because of the pandemic nature of the virus. One of the preventive measures during a pandemic is to quarantine the asymptotic people so that the other healthypeople can be safe and also stops further spreading. The quarantine also helps the medical team to monitor the quarantined person's vital health parameters continuously everyday and provide him with the required medication and in case of emergency remedial measures can be instantiated.A health monitoring system is a useful tool in monitoring the Quarantined people. In this survey paper, the focus is on the approaches used in various implementations of monitoring of Quarantined people.